1975
DOI: 10.1159/000169701
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Caliber

Abstract: Many aspects of vascular caliber can be accounted for on the basis of interactions between the frictional drag generated by the stream, and the sensitivity of the endothelial cells to this force. When the drag force on endothelial cells is at its critical set-point, these lining cells are at rest with respect to factors that affect caliber. An increase in flow rate increases the drag and appears to induce the endothelium to generate a signal that triggers relaxation of the subjacent medial smooth muscle. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
135
1
2

Year Published

1982
1982
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 234 publications
(147 citation statements)
references
References 40 publications
9
135
1
2
Order By: Relevance
“…1,18 In reality, vascular reactions may be coupled in several respects, as indicated by additional links in Figure 2B and 2C: (i) the circumferential stress increases with increasing diameter, in accordance with the Law of Laplace; (ii) changes in diameter may be coupled to changes of wall thickness, and vice versa; 5,19 (iii) biological responses to and may depend on wall thickness which affects the diffusion into smooth muscle of substances produced by endothelial cells. Also, wall structure, including the distribution of passive load-bearing elements in the wall, and hence the distribution of stress, may vary with wall thickness; (iv) responses to the metabolic stimulus may involve both diameter and wall mass; and (v) changes in may elicit changes in wall mass, and changes in may lead to diameter changes.…”
Section: Development Of a Model For Structural Adaptationmentioning
confidence: 94%
“…1,18 In reality, vascular reactions may be coupled in several respects, as indicated by additional links in Figure 2B and 2C: (i) the circumferential stress increases with increasing diameter, in accordance with the Law of Laplace; (ii) changes in diameter may be coupled to changes of wall thickness, and vice versa; 5,19 (iii) biological responses to and may depend on wall thickness which affects the diffusion into smooth muscle of substances produced by endothelial cells. Also, wall structure, including the distribution of passive load-bearing elements in the wall, and hence the distribution of stress, may vary with wall thickness; (iv) responses to the metabolic stimulus may involve both diameter and wall mass; and (v) changes in may elicit changes in wall mass, and changes in may lead to diameter changes.…”
Section: Development Of a Model For Structural Adaptationmentioning
confidence: 94%
“…However, different values for the exponent T have been reported in the literature. Measurements on corrosion casts of human coronary arteries (Smaje, Fraser, and Clough, 1980) indicated that ,/ = 3.0, which would allow for uniform shear stress all over the tree (Rodbard, 1975). Conversely, it has been argued that minimum reflection of pulse waves (Arts, Kruger, Gerven, Lambregts, and Reneman, 1979) would be achieved with T = 2.55.…”
Section: Constraints For Radii At Bifurcationsmentioning
confidence: 99%
“…These studies have established that hemodynamic loading such as wall shear stress (τ w ), which is sensed by endothelial cells, acts to initiate signal transduction pathways leading to the regulation of vessel growth (Culver and Dickinson 2010;Groenendijk et al 2004;Poelmann et al 2008). Though the exact molecular mechanisms involved in the relationship between aortic arch hemodynamics, gene expression, and tissue remodeling are not yet fully understood, τ w is believed to be the primary mechanical stimulus for vascular remodeling (Culver and Dickinson 2010;Rodbard 1975), clinically referred to as the "flow-dependency principle" (Kamiya and Togawa 1980;Lu et al 2001;Rodbard 1975). The temporal and spatial events associated with flow sensitive altered aortic morphogenesis (at the first aortic arch) in the Akl-1 mutant zebrafish model can be more complex as illustrated by recent studies Corti et al 2011;Patrick et al 2011).…”
Section: Introductionmentioning
confidence: 99%